UPAYA PENCEGAHAN PERNIKAHAN DINI MELALUI SEMINAR PRA- NIKAH SE-DESA CIBEBER CIKALONG TASIKMALAYA - Muhamad Reza Atqia; Muhammad Ali Kandiyas, Muhamad Jauhari Abdu Rahman, Moch Zahran Zain Almutawakkil (JOURNAL OF COMMUNITY DEDICATION, 2024)
Marriage is a noble thing that unites men and women physically and mentally. However, this should not have the impact of violating other things, such as the minimum age limit for marriage, because this can be categorized as early marriage. If things fall into the category of early marriage, then the negative impact will be felt more by the couple, including on physical health, emotional mental health, educational disruption, reproductive disorders, and social welfare. The method for implementing community service is carried out in the preparation, implementation and evaluation stages. The KKN Team of the As-Sa'adah Sukasari Sumedang Sharia Science College carries out community service in order to prevent early marriage through pre-marriage seminar activities throughout the Cibeber Cikalong Tasikmalaya Village, involving the village, KUA, community health center and police station. The participants consisted of 60 representative students from junior and senior high schools in the Cibeber Village area.